EDUKASI DAN PELATIHAN PENYUSUNAN STANDAR OPERASIONAL PROSEDUR (SOP) DI DESA SUKMA KECAMATAN BOTUPINGGE KABUPATEN BONE BOLANGO - Imam Mashudi; Tri Setiawati Maulana (LPPM Universitas Bina Mandiri Gorontalo, 2024)
The Implementation of the training The Sukma Village community has not fully had awareness of standard operating procedures (SOP). This community service aims to provide education and training on the benefits and importance of knowledge, and training on standard operating procedures. The method used in providing education and training to the people in Sukma Village is a bottom-up method in which to do the following: 1) make observations of the place of service first; 2) forming a team of proposers; 3) prepare participants; 4) carry out material readiness; 5) perform monitoring and evaluation. The results of the implementation of community service activities that have been carried out for three days The community has begun to understand the importance of standard operating procedures in social life. As well as running several examples of standard operating procedures (SOP) in the village environment. And shows a change in attitude and understanding of the village community about. 1) efforts to carry out standard operating procedures (SOP) in a good and correct way within the village structure; 2) conduct education and training for people who do not understand how to implement the SOP itself.